RE-AIM Planning and Evaluation Framework: Adapting to New Science and Practice With a 20-Year Review - Glasgow, Russell E.; Harden, Samantha M.; Gaglio, Bridget; Rabin, Borsika; Smith, Matthew Lee; Porter, Gwenndolyn C.; Ory, Marcia G.; Estabrooks, Paul A. (Frontiers in Public Health, 2019)
The RE-AIM planning and evaluation public health framework was conceptualized over two decades ago. As one of the most frequently applied implementation frameworks, RE-AIM has now been cited in over 2,800 publications. This paper describes the application and evolution of RE-AIM as well as lessons learned from its use. RE-AIM has been applied most often in public health and health behavior change research, but increasingly in more diverse content areas and within clinical, community, and corporate settings. We discuss challenges of using RE-AIM while encouraging a more pragmatic use of key dimensions rather than comprehensive applications of all elements. Current foci of RE-AIM include increasing the emphasis on cost and adaptations to programs and expanding the use of qualitative methods to understand the “how” and “why.” The framework will continue to evolve to focus on contextual and explanatory factors related to RE-AIM outcomes, package RE-AIM for use by non-researchers, and integrate RE-AIM with other pragmatic and reporting frameworks.